On the Nature of Bifurcation in a Ratio-Dependent Predator-Prey Model with Delays - Changjin Xu; Yusen Wu (Journal of Applied Mathematics)
A ratio-dependent predator-prey model with two delays is investigated. The conditions which ensure the local stability and the existence of Hopf bifurcation at the positive equilibrium of the system are obtained. It shows that the two different time delays have different effects on the dynamical behavior of the system. An example together with its numerical simulations shows the feasibility of the main results. Finally, main conclusions are included.